Alberto Caeiro’s philosophy without philosophy - Rivera Muriel, Juan Fernando (Estudios de Filosofía, 2013)
The work of the poet Alberto Caeiro, Fernando Pessoa’s heteronymous “master”, is a philosophy without philosophy. One that puts into question the cultural tradition that “covers” thought: philosophy, poetry, mysticism, religion. It does so by returning to nature in a way that implies an absence of meaning, concepts, knowledge structures and prejudices that distort the look of things, the experience of Nature and feel of Reality. Because it deals with an unlearning, Caeiro turns to the simple, to the tautological, not-thinking, almost to the absence of the word.